Sham Fights and Mock Sieges: An Enduring Antiquity in the Medieval and Pre-modern Representation of War - Adami, Giuseppe (Drammaturgia, 2020)
The article examines the centuries-old relationships between the world of war and the world of spectacle. It analyses different examples of sham fights and mock sieges, which belong both to Roman times as well as the medieval and pre-modern periods. The aim of this analysis is to show how over the course of time these military events remained essentially unchanged, being tied by common organisational and ideological threads. The ritualised exhibition of war in the ancient and late ancient world is thus reflected in the ethos of the medieval ‘bellatores’, remaining almost entirely the same up to the emergence of the better known examples of the gentleman soldier and the official of pre-modern armies. The festive and spectacular aspects of such performances consolidated the military world’s resilience to change, surviving the countless transformations that might have questioned its identity.